A PC- based simulation package for engineering students and professionals on compressible flow (2003)
Both Engineering students and practicing Engineers are involved in the design and analysis associated with fluid mechanics and thermo-dynamics problems. For them to be very efficient and proficient in handling various problems there is need for scientific data and general information in forms of tables or graphs. These must be made available in a compact form. In this paper a successful attempt was made to make available this aforementioned data in respect of compressible flow. All the equations concerned are brought together in a simplified form and programmed to generate useful data for various gases of interest on compressible flows. Analysis of compressible fluid flow becomes very easy if one has access to information as presented in this paper.